2020
DOI: 10.1016/j.jacbts.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Von Willebrand Factor Influences Inflammatory Endothelial Activation and Vascular Compliance in Atherosclerosis

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In animal models of hyperlipidemia, vWF-mediated platelet adhesion is known to accelerate atherosclerosis and to promote the recruitment of cells of the innate immune system to areas of plaque formation. 6 , 8 , 9 Accordingly, the increase in aortic root plaque formation seen in LDLR −/− AD13 −/− mice was not unexpected and, in many cases, there appeared to be an extension of plaque onto the valve leaflet surface. Yet, most of the valve thickening in LDLR −/− AD13 −/− mice was attributable not to inflammatory plaque formation, but rather to extensive proliferation of VICs with evidence for myofibroblastic and osteogenic transformation, an expansion of collagen-rich matrix, MMP-9 up-regulation, and microcalcification.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In animal models of hyperlipidemia, vWF-mediated platelet adhesion is known to accelerate atherosclerosis and to promote the recruitment of cells of the innate immune system to areas of plaque formation. 6 , 8 , 9 Accordingly, the increase in aortic root plaque formation seen in LDLR −/− AD13 −/− mice was not unexpected and, in many cases, there appeared to be an extension of plaque onto the valve leaflet surface. Yet, most of the valve thickening in LDLR −/− AD13 −/− mice was attributable not to inflammatory plaque formation, but rather to extensive proliferation of VICs with evidence for myofibroblastic and osteogenic transformation, an expansion of collagen-rich matrix, MMP-9 up-regulation, and microcalcification.…”
Section: Discussionmentioning
confidence: 92%
“…We evaluated hyperlipidemic mice deficient for LDLR fed a WSD that not only develop atherosclerosis but also have increased endothelial-associated vWF and adhesion of platelets to the arterial wall. 8 , 12 The additional genetic deletion of ADAMTS13 in these mice has been shown to markedly increase vWF-mediated platelet adhesion in the aorta and the development of large vessel atherosclerosis. 8 , 9 In the current study, LDLR −/− AD13 −/− mice on WSD demonstrated extensive vWF not only in atherosclerotic lesions, but also on VECs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The role of vWF and ADAMTS13 in atherosclerosis has also been recently proven in low-density lipoprotein receptor-deficient mice crossed with mice deficient for ADAMTS13, who were then treated with recombinant ADAMTS13. Following its administration, a reduction in endothelial vWF and platelet adhesion was noted, leading to a significant decrease in aortic plaque size [38].…”
Section: Endothelial Dysfunction and Platelet Activationmentioning
confidence: 99%